2002
DOI: 10.1002/ana.10144
|View full text |Cite
|
Sign up to set email alerts
|

Functional recovery and neuroanatomical plasticity following middle cerebral artery occlusion and IN‐1 antibody treatment in the adult rat

Abstract: Stroke is a prevalent and devastating disorder, and no treatment is currently available to restore lost neuronal function after stroke occurs. One unique therapy that may improve functional recovery after stroke is blockade of the neurite inhibitory protein Nogo-A with the monoclonal antibody IN-1, through enhancement of neuroanatomical plasticity from uninjured areas of the central nervous system. In the present study, we combined IN-1 treatment with an ischemic lesion (permanent middle cerebral artery occlus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
233
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(253 citation statements)
references
References 59 publications
20
233
0
Order By: Relevance
“…The NgR fusion protein binding to myelin inhibitors does not incite an experimental allergic encephalitis-like loss of function, and histologic examination of NgR(310)Ecto-Fctreated brain reveals no increased inflammation and no white matter loss (data not shown). The behavioral and anatomical results obtained here with Nogo-NgR perturbation are similar to, but of greater magnitude than, those observed with anti-Nogo-A antibodies (Papadopoulos et al, 2002;Wiessner et al, 2003). These antibodies target an independent activity of the amino-Nogo domain of Nogo-A, but they may impinge allosterically on Nogo-66 signaling (Fournier et al, 2001;Wiessner et al, 2003).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The NgR fusion protein binding to myelin inhibitors does not incite an experimental allergic encephalitis-like loss of function, and histologic examination of NgR(310)Ecto-Fctreated brain reveals no increased inflammation and no white matter loss (data not shown). The behavioral and anatomical results obtained here with Nogo-NgR perturbation are similar to, but of greater magnitude than, those observed with anti-Nogo-A antibodies (Papadopoulos et al, 2002;Wiessner et al, 2003). These antibodies target an independent activity of the amino-Nogo domain of Nogo-A, but they may impinge allosterically on Nogo-66 signaling (Fournier et al, 2001;Wiessner et al, 2003).…”
Section: Discussionsupporting
confidence: 76%
“…There have been previous reports of some benefit from antiNogo antibody treatment of rats with middle cerebral artery occlusion (MCAO) (Papadopoulos et al, 2002;Wiessner et al, 2003). No genetic analysis of the Nogo-NgR system has been made in stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Following ischemic lesions, the adult CNS can induce cellular responses needed for neurite growth and synaptic formation (Cramer and Chopp, 2000), including the expression of growth-promoting factors, such as BDNF (Comelli et al, 1993) and basic fibroblast growth factor (bFGF) (Lin et al, 1997) that could lead to partial spontaneous functional recovery. Related studies have indicated that functional recovery in rodent ischemic stroke models is associated with collateral sprouting of the uninjured CST to the denervated side of spinal cord and is enhanced by treatment of inosine , bFGF (Kawamata et al, 1997), Nogo antibody (Papadopoulos et al, 2002) and Nogo receptor antagonist (Lee et al, 2004). Based on our and other studies, the BMSCs transplanted into the ischemic brain environment may provide their beneficial effects by secretion of neurotrophins and growth factors, including BDNF (Dormady et al, 2001;Li et al, 2002) and VEGF (Chen et al, 2003a).…”
Section: Discussionmentioning
confidence: 58%
“…Growth of intact CST fibers into the denervated brainstem and cervical spinal cord after unilateral corticospinal tract lesion (pyramidotomy) and restitution of fine motor skill were observed in adult rats treated with IN-1 [39][40][41][42] and in mice null mutant for nogo-a and ngr1 [43]. Perhaps the most convincing data illustrating a functional role for de novo growth of intact fiber systems come from stroke studies that have shown the potent effects of both IN-1 [44,45] and NgR(310)ecto-Fc [46] on functional restoration after middle cerebral artery occlusion. Common to all these studies is the efficacy of treatment in restoring function post-lesion.…”
Section: Myelin-associated Inhibitors and Axonal Growthmentioning
confidence: 99%